Tingkat Kecemasan Atlet Judo Kota Salatiga Sebelum Menghadapi Pertandingan (Indonesian Journal for Physical Education and Sport, 2022)
The background of the problem in this study is, all Judo athletes in Salatiga City have faced a match. Many athletes experience anxiety before facing a match. The formulation of the problem in this research is how much anxiety level of Judo athletes in Salatiga City before facing a match? The purpose of this study was to find out how much anxiety level of Judo athletes in Salatiga City was before facing a match. This study uses a quantitative method with a correlation design and sampling with a total sampling technique. Data collection using questionnaires and data analysis techniques using descriptive statistics. The results showed that the level of concern was 73,5%, wich was inthe high category. The level of concentration disturbance was 60,2%, which is in the moderate category. And the level of somatic anxiety was 68,9%, is in the high category. Data obtained from athlete’s anxiety levels, 8 athletes (40%) were at the moderte level and 12 athletes (60%) were at the high level. The average anxiet level of Judo athletes in Salatiga City is 49,2, in the high category.